Q&A. (Smithsonian, 2010)
An interview with Irish artist John Gerrard is presented and it is reported that his work is on display at the Hirshhorn Museum, Washington, D.C. until May 31, 2010. When asked about his artwork, he describes it as virtual reality. He reports that his art is labor-intensive to create and that he collaborates with a 3-D modeler and a computer programmer. He comments on his theme of American West landscapes.